Therapeutic strategies for coping with sexual dysfunctions in women: systematic review (Revista Científica Integrada, 2024)
Objective: to identify therapeutic strategies for coping with sexual dysfunctions in women. Method: systematic review, conducted in the LILACS, PubMed/MEDLINE and EMBASE databases, and in the Virtual Health Library, focusing on therapeutic strategies for sexual dysfunctions in adult women. The time frame for identifying the works was from January 2013 to September 2023, with articles from literature reviews, case studies, course completion works, and experience reports being excluded from the search. Results: 1,373 works were found, but after reading them completely and applying the eligibility criteria, the sample comprised 40 articles, with 10,808 women. The main complaints that led to sexual dysfunctions were dyspareunia and vulvovaginal dryness. The most common therapeutic strategies were treatments based on estrogen or phytoestrogens, hormone therapy, neuromodulators, pelvic floor physiotherapy, moisturizing creams, or vaginal lubricants. Conclusion: different strategies have been used to treat sexual dysfunctions, especially those with estrogen. Further investigations that consider personalized treatments and non-pharmacological therapies need to be encouraged.
Keywords: Physiological sexual dysfunctions; Woman; Therapeutics; Helping behavior